Anthropometric Profile, Body Composition and Somatotype of Elite ILCA 7 Class Sailors—Differences Across General Competitive Success Levels - Luka Pezelj; Jan G. Bourgois; Mirjana Milić; Josip Maleš; Israel Caraballo (Applied Sciences, 2025)
Setting up anthropometric profiles for elite athletes in each sport, sport discipline, or specific sport positions could be a key element of sport selection processes. The main purpose of this study was to determine the anthropometric characteristics, body composition, and somatotype profiles of elite international ILCA 7 class sailors and to determine the differences contributing to different levels of competitive success. The subject sample included 97 elite ILCA 7 class sailors. A set of 25 anthropometric variables was applied. The sailors were divided into three groups according to their level of general competitive success according to the World Sailing Rankings. Differences between elite ILCA 7 sailors, separated into Higher, Medium, and Lower groups based on their success, were found in terms of age, body mass, muscle mass, trunk muscle mass, leg muscle mass, biepicondilar humerus width, sum of skinfolds, triceps skinfold, supraspinale skinfold, medial calf skinfold, and endomorphy rating. The most successful group of sailors was, on average, 4.9 years older than the least successful group. More highly successful sailors were also found to have an average of 2.73 kg more muscle mass but an 8.81 mm lower sum of skinfolds than those in the lower success group. Considering the average values of somatotype categories, ILCA 7 sailors fit the endomorphic–mesomorph somatotype category (3.23 ± 0.99–4.81 ± 0.90–2.25 ± 0.86). This research clearly identifies the anthropometric profile of elite ILCA 7 sailors, which can significantly contribute to a more informed choice of sailing class. Given the results of this research, current ILCA 7 sailors can easily compare their own anthropometric parameters with elite ILCA 7 sailors and eventually adjust their training process to obtain a more desirable anthropometric profile.